IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH THE APPLICATION OF WORD WALL STRATEGY TO THE TENTH GRADE STUDENTS OF SMA GKPI PAMEN MEDAN - Tamba, Nofita; Ginting, Fiber Yun Almanda; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2022)
Learning vocabulary is important for learners because the mastery of certain words would motivate them to express themselves clearly. In reality, vocabulary becomes a problem to almost all of students at any level of education. This study is aimed to improve students’ vocabulary mastery through Word Wall Strategy. This strategy is one of appropriate stategies in improving students’ vocabulary mastery. The subject of this study is the students of Class X A of SMA GKPI Pamen Medan in the Academic Year of 2017/2018. This study was conducted by applying Classroom Action Research (CAR), which was performed in two cycles (cycle I and cycle II) and each cycle consisted of three meetings, excluding pretest and posttest. The instruments of collecting data are vocabulary tests, field notes, observation sheet, documentation, and questionaire. The results of vocabulary tests showed that the mean of the students’ score increased continuously from pretest is 59 with 15% of students who got score >75, in formative test in cycle I is 67.63 with 45% of students who got score >75, and in the posttest is 83.33 with 91% of students who got score >75. It showed that there is a significant mean score increase from pretest to posttest, namely about 76%. The field notes, observation sheet, photograph evidence and questionaire showed that the students are interested in the learning teaching processes through the application Word Wall Strategy. It was found that Word Wall Strategy could improve students’ vocabulary mastery. It is suggested that teachers of English apply Word Wall strategy as one of the strategies in teaching vocabulary mastery.